Institute of Archaeology (University of London). Twenty-second Annual Report. 1 August 1964-31 July 1965 - Anonymus, A. (1967)
spez. 151-152: Western Asiatic Archaeology (S. Lloyd; B.Parker; P. J. Parr; J. Mellaart; K. R. Maxwell-Hyslop).